2009
DOI: 10.1097/ijg.0b013e318181545e
|View full text |Cite
|
Sign up to set email alerts
|

Variance Owing to Observer, Repeat Imaging, and Fundus Camera Type on Cup-to-disc Ratio Estimates by Stereo Planimetry

Abstract: Interobserver variability was the largest source of variation for glaucoma specialists, whereas their interrepeat and intercamera variability is comparable with that of the algorithm. DAP reduces variability on LCDR estimates from simultaneous stereo images, such as the Nidek 3Dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…In this study, the reference standard was set by a single expert. We have previously shown that there is substantial interobserver variability of planimetry of the optic disc in stereo color fundus photographs [2]. By training the automatic method on the segmentations from a single expert observer, the method produces results that are biased towards the opinion of this observer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the reference standard was set by a single expert. We have previously shown that there is substantial interobserver variability of planimetry of the optic disc in stereo color fundus photographs [2]. By training the automatic method on the segmentations from a single expert observer, the method produces results that are biased towards the opinion of this observer.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of the optic disc cup and rim surfaces, or cup-to-disc ratio in these images is an important structural indicator for assessing the presence of glaucoma and may help in quantifying the progression of glaucoma. To quantify the ratio, planimetry has commonly been performed by glaucoma specialists from stereo color photographs of the optic disc [2]. However, we and others have previously shown that manual planimetry is time-consuming with substantial interobserver variability [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, we and others have previously shown that manual planimetry is time-consuming and introduces substantial inter-observer variability due to the need for human interpretation. 4,5 Merickel et al developed a 2-D automated system for the segmentation of the optic disc margin (and cup) on stereo fundus disc photographs. 6 They used a soft pixel classification method to generate a probability map of the disc and segmented the disc using a graph search method upon the probability map image.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that use of visual estimation for assessment of infected toenails may be a source of error in determining onychomycosis efficacy (1,2). Significant intra-observer differences have been noted in assessments of nail disease characteristics, as well as other medical fields (3)(4)(5). Despite the issues with visual assessment, few published works support the need for objective measures of affected areas in onychomycosis, or illustrate the validity of objective solutions (1).…”
Section: Introductionmentioning
confidence: 97%